Pengaruh Pelatihan Kesehatan Dan Keselamatan Kerja Terhadap Kinerja Pekerja Konstruksi - Panggabean, Diani Sari; Dwi Syahputri Purba; Meutia Hafni Indah Triana; Abdurrozzaq Hasibuan (STIKES Columbia Asia Medan, 2025)
The construction sector is one of the industries with the highest risk of workplace accidents in Indonesia, contributing approximately 32% of the total national incidents. This study aims to analyze the effect of Occupational Health and Safety (OHS) training on worker performance in the construction sector. A literature review method was employed by collecting seven national research articles published between 2019 and 2025 through the Google Scholar database. The findings indicate that OHS training has a significant and positive impact on enhancing the performance of construction workers. It not only improves technical knowledge and skills but also fosters a stronger safety-oriented attitude, increases workers' sense of responsibility, and reduces the risk of workplace accidents. Structured and consistent training helps create a safer and more efficient work environment, ultimately contributing to improved work effectiveness and the overall sustainability of construction projects. This study underscores the importance of implementing OHS training programs as a key strategy to improve worker performance in the construction industry.